Efforts to Identify and Combat Antimicrobial Resistance in Uganda: A Systematic Review - Tefero Kivumbi, Mark; Standley, Claire J. (Tropical Medicine and Infectious Disease, 2021)
The global burden of antimicrobial resistance is on the rise, resulting in higher morbidity and mortality in our communities. The spread of antimicrobial resistance in the environment and development of resistant microbes is a challenge to the control of antimicrobial resistance. Approaches, such as antimicrobial stewardship programmes and enhanced surveillance, have been devised to curb its spread. However, particularly in lower- and middle-income countries, the overall extent of antimicrobial resistance and knowledge on ongoing surveillance, stewardship or investigation efforts, are often poorly understood. This study aimed to look at the efforts that have been undertaken to detect and combat antimicrobial resistance in Uganda as a means of establishing an overview of the situation, to help inform future decisions. We conducted a systematic literature review of the PubMed database to assess these efforts. A search combining keywords associated with antimicrobial resistance were used to find relevant studies between 1995 and 2020 on surveillance of antimicrobial resistance in Uganda, and susceptibility of microbes to different drugs. The search yielded 430 records, 163 of which met the inclusion criteria for analysis. The studies were categorized according to country and region, the type of antimicrobial resistance, context of the study, study design and outcome of the study. We observed that antibacterial resistance and antimalarial resistance had the most published studies while antiviral and antifungal resistance were represented by very few studies each. Most studies were conducted in humans and hospital settings, with few in veterinary and One Health contexts, and only one that included environmental sampling. The majority of studies have focused on surveillance, susceptibility testing or resistance genes; none of our included papers had a policy or stewardship focus. The results from our work can inform public health policy on antimicrobial stewardship as it contributes to understanding the status of antimicrobial resistance surveillance in Uganda, and can also help to guide future research efforts. Notably, a One Health approach needs to be followed with respect to surveillance of antimicrobial resistance to better understand the mechanisms of resistance transfer across the human-animal–environment interface, including additional investigation in antiviral and antifungal resistance.